Bebida à base de gergelim e fruta: desenvolvimento, caracterização e aceitabilidade - Ferreira, Luan Costa (2017)
There is a growing consumer concern with health issues. The sesame (Sesamum indicum L.), despite having high levels of minerals, fibers and unsaturated fats, is often underutilized in Brazil. Thus, the objective of this study is to produce a drink based on water-soluble sesame extract (EHG) and orange (Citrus sinensis), with adequate levels of calcium, magnesium and phosphorus and vitamin C, for people with food restrictions or not. Through the experimental planning, combining levels of the independent variables: EHG concentration and orange liquid concentrate and considering as dependent variables the levels of calcium and vitamin C in beverages, was defined as formulations (actual value of sesame/orange liquid concentrate for 100 mL) for F4 (14.28g/45mL), F6 (15.64g/27.5mL) and F8 (10.98g/52.24mL) for sensitivity analysis by presenting satisfactory mineral and vitamin values. If the acceptance of the attributes of color, aroma, flavor, sweetness, viscosity and overall impression, besides the intention of consumption, comparing as means obtained between the public with restrictive diets and general public. It was characterized by a more accepted formulation (F4) for moisture content, proteins, lipids, carbohydrates and ashes. Such formulation had 52.24% orange liquid concentrate and 10.98% sesame, obtained its extract, the degree of its composition 82.34% of humidity, 15.02% of carbohydrates, 1.56% of lipids , 0.86% protein and 0.22% ash. It also presented 39.72 mg of calcium, 128.45 mg of phosphorus, 38.63 mg of magnesium and 26 mg of vitamin C in the 200 mL portion. However, the public with restrictive diets presented averages, for a global impression, between the "mildly liked" and "highly liked" hedonic terms and the general public among the hedonic terms "liked slightly" and "liked moderately." This difference was statistically significant (p <0.0001). Differences in flavor (P <0.05), sweetness (p <0.01) and the consumption attitude of the drinks (p <0.00005), with a higher preference of the product by the public with food restrictions. Thus, the orange drink with developed EHG has the potential to compete directly with other products obtained from seed or grain extracts because it presents satisfactory acceptance and intention to consume, mainly by people with restrictive diets, as well as good amounts of minerals and vitamin C.